Acute neuro care : focused approach to neuroemergencies - Bidkar, Prasanna Udupi; Vanamoorthy, Ponniah (Springer, 2020)
The book provides detailed information on all major neuroemergencies, and includes a detailed checklist for practical care during the first hour of an emergency. Reinforcing the concept of quality care for better outcomes in patients with neurological diseases, the book discusses approaches to comatose patients, neurological evaluation, neuropharmacology, neuroradiology, traumatic brain and spine injury, and various other neurological disorders. The field of neuroanesthesiology and neurocritical care has expanded with the advent of newer, complex surgeries, and neurocritical care is becoming an established subspecialty of neuroscience. Neurological emergencies require special care since prevention of secondary damage to the brain is of paramount importance. A valuable resource for intensivists, neurointensivists, emergency medicine physicians, neurology and neurosurgeons and nursing professionals involved in neurocare, this book also serves as study material forparticipants of the two-day course on "Acute Neuro Care" designed by the Indian Society of Neuroanesthesiology and Critical Care (ISNACC)